2018
DOI: 10.3390/ijms19102898
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Protects Mesenchymal Stem Cells against P-Cresol-Induced Mitochondrial Dysfunction via Up-Regulation of PINK-1

Abstract: Mesenchymal stem cells (MSC) could be a candidate for cell-based therapy in chronic kidney disease (CKD); however, the uremic toxin in patients with CKD restricts the therapeutic efficacy of MSCs. To address this problem, we explored the effect of pioglitazone as a measure against exposure to the uremic toxin P-cresol (PC) in MSCs. Under PC exposure conditions, apoptosis of MSCs was induced, as well as PC-induced dysfunction of mitochondria by augmentation of mitofusion, reduction of mitophagy, and inactivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 40 publications
3
22
0
Order By: Relevance
“…Moreover, damaged DNA produced from the nuclei of senescent cells may stimulate inflammatory pathways and finally lead to apoptosis. Our model shows that apoptosis-associated proteins are significantly expressed in PC-treated DPSCs, which is consistent with an earlier report [56].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, damaged DNA produced from the nuclei of senescent cells may stimulate inflammatory pathways and finally lead to apoptosis. Our model shows that apoptosis-associated proteins are significantly expressed in PC-treated DPSCs, which is consistent with an earlier report [56].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, effective DPSCs-based therapy in aged patients should be enhanced; we recently used CCR3 antagonist to retreat the adverse effects of PC on periodontal ligament cells, resulting in enhanced pulp regeneration in aged dogs [29]. In addition, other substances such as fucoidan, pioglitazone, and melatonin showed protective effects against PC-induced cellular senescence in MSCs [28,56,62]. Taken together, substances and molecules that can restore regenerative DPSCs and reserve their physiology against PC-induced senescence should be used in aged individuals, especially those with uremia.…”
Section: Discussionmentioning
confidence: 99%
“…CKD induces the progressive loss of function in kidneys resulting in ineffective homeostasis in the body. CKD‐induced uremic toxins, such as indoxyl sulfate and p‐cresol, hamper the biological activities of MSCs and lead to cardiovascular disease, weakened bones, malfunctioning central nervous system, and improper inflammation in patients . The regenerative potential of CKD‐MSCs is also suppressed in a murine ischemic injury .…”
Section: Discussionmentioning
confidence: 99%
“…system, and improper inflammation in patients. 12,13 The regenerative potential of CKD-MSCs is also suppressed in a murine ischemic injury. 10,14 Consistent with these findings, our results have shown that biological functions like senescence, proliferation, and mitochondrial activity were significantly decreased in CKD-MSCs and treatment with MT exosomes drastically improved these CKD-mediated pathophysiological conditions.…”
Section: Mt Exosome-treated Ckd-mscs Improved the Functional Recovementioning
confidence: 99%
“…In CKD patients, the damaged kidney secretes uremic toxics such as indoxyl sulfate and P-cresol, and the accumulation of these toxins causes various complications. Our previous studies proved that P-cresol, a low molecular weight uremic toxin with high affinity to protein, reduced cellular functions by various mechanisms, including accumulated reactive oxygen species (ROS), cell senescence, abnormal mitochondria, and endoplasmic reticulum stress [4][5][6]. Therefore, in the treatment of CKD patients, it is important to protect renal proximal tubule epithelial cells against damages caused by uremic toxins.…”
Section: Introductionmentioning
confidence: 99%